LEARNERS’ SPEAKING PROBLEM IN ENGLISH CLASS ON PERBANKAN SYARIAH DEPARTMENT AT ANNUQAYAH UNIVERSITY OF GULUK-GULUK SUMENEP: Learners’ speaking problem in English Class On perbankan syariah department at Annuqayah University of Guluk-guluk Sumenep - Achmad Syarofi Al-Furqon; Firdausiyah Firdausiyah; Jaftiyatur Rohaniyah; Zainollah (Universitas Madura, 2026)
As a foreign language, English is taught from elementary through university. Speaking is one of part in English skill that also taught for university learners, especially on Perbankan Syariah department at Annuqayyah university. The purpose of this study is to investigate what the learner’s problem faced in speaking English and what the factor that contribute the learner’s have difficulties in speaking English. The research method is qualitative and it uses purposive sampling. Furthermore, the finding shows that there are four problems faced by students in speaking English, they are: 1) Inhibition, 2) Nothing to say, 3) Low or Uneven participation, and 4) Mother tongue use. And there are two factors led to students’ difficulties in speaking English, they are: 1) Cognitive style, and 2) Personality.